Analisis Keselamatan dan Kesehatan Kerja dengan Metode Job Safety Analysis pada Proyek Bendungan Kuwil Kawangkoan - Mukhamad Afif Salim; Agus Bambang Siswanto; Tigo Mindiastiwi; Purwantini Purwantini (Fakultas Teknik, 2023)
The Kuwil Kawangkoan Dam Development Project is one of the National Strategic Projects (PSN). The Kuwil Kawangkoan Dam is a dam located in North Sulawesi province, in the district/city of North Minahasa. This dam is planned to have a capacity of 23.37M³ and is expected to reduce flood discharge by 282 M³/second, provide raw water supply of 4.50 M³/second, and generate electricity of 1.20 MW. With the large-scale development of the Kuwil Kawangkoan Dam Development Project and the high level of risk of work accidents in this development, it is necessary to have an analysis of occupational health and safety (K3). The type of research used is descriptive observational research to identify hazards and analyze the risk of work accidents Hazard identification uses Job Safety Analysis (JSA) technique, which is a method of safety analysis by identifying hazards in a job and controlling work accidents that occur while working. The results of this research are the selection of 6 jobs which previously detailed the stages of the work first and then analyzed the identification of the level of risk so that the results obtained in the Kuwil kawangkoan Dam Development Project there are 3 levels of risk categories, namely extreme risk, high risk and moderate risk. For extreme risk levels, there are 5 jobs with a total of 18 potential hazards. High and moderate risk levels are found in 6 jobs with a total of 84 potential hazards for high risk levels and 29 potential hazards for medium risk levels. As for risk control, it is categorized into 3 aspects, namely the worker aspect, the work environment aspect and the equipment and material aspects of the project